Gestão contemporânea de carreira: um estudo de caso com peritos criminais do Instituto Nacional de Criminalística da Polícia Federal - Lima, Marcos Vinicius Garcia Rodrigues (2013)
In the past three decades the debate about career management has intensified between scholars. The social, economic, technological changes and their influence on the labor market have sha r pened the interest of organizational researchers to understand how i ndividuals conduct their careers in this new climate. The notion of personal responsibility in managing their own career becomes relevant, reducing the organization's role in this process. Flexibility, self - awareness and openness to job mobility are new re quirements. Two models that express this reality emerge: the protean and boundaryless careers . This study aimed to explore how workers from a Brazilian law enforcement federal agency – the forensic experts from the Federal Police National Institute of Crimi nalistics – manage their careers in the light of such phenomena, considering the traditional organizational environment in which they are immersed. Aspects of career commitment and career entrenchment were also considered. We opted to use qualitative case s tudy and document research. Eleven in - depth interviews were conducted, whose content was analyzed according to a pre - established thematic grid. The results reveal that protean and boundaryless career attitudes were identified even with the rigid career mod el of Brazilian federal public sector . Furthermore, there is evidence of voluntary career entrenchment , without, however, affecting career commitment. The research aims to open up new possibilities of understanding careers in the Brazilian public sector, e specially considering the peculiarities of law enforcement careers